Composition, technology and research development dental powder - Gerchak В. В.; Grynovets І. С.; Shostak Т. А.; Grynovets В. С. (Actual Dentistry, 2022)
Summary. Oral hygiene is a complex set of preventive measures that involve usage of objects and means aimed at preventing the development of pathological processes in the oral cavity. For oral hygiene, a complex of products is used: tooth powders, pastes, gels, rinses, elixirs, balsams, chewing gum and care items—toothbrushes, dental floss, intradental brushes and toothpicks. Tooth powders are made from chemically precipitated chalk (calcium or magnesium carbonate), both abrasive components and various excipients (biologically active substances, fillers, adsorbents, flavors, bleaches, dyes, flavors, anti-inflammatory and flavor components). Hygienic form in the form of tooth powder in comparison with other forms of release (balms, gels, solutions, pastes) has the ability to better clean the tooth enamel surface. Powder such a tool cleans the surface of the teeth not only from soft plaque, but also from hard, and neutralizes the acids formed in the oral cavity, thus regulating the microbiocenosis. In addition, it has disinfectant and deodorizing properties. The conducted research allowed to develop the optimized structure, technology of hygienic for itself in the form of tooth powder. Tooth powder with extract Salvia officinalis will prevent diseases of the oral cavity of various etiology, thoroughly remove plaque, regulate microbiocenosis and give a pleasant smell and flavor—will refresh the breath. And also to control the quality of tooth powder with Salvia officinalis extract. In particular, the quality control of tooth powders was carried out in accordance with the requirements of the regulatory documentation of GOST 592-77 “Tooth powder” and organoleptic and physicochemical parameters.